2011
DOI: 10.1007/s12562-011-0324-0
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in otolith and somatic growth in age-0 Pacific saury Cololabis saira

Abstract: We evaluated the seasonal changes in otolith

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The right otolith was embedded in epoxy resin and the incidence of an annual ring determined using light microscopy following Suyama et al (2012a, b). Because formation of the annual ring commences in September (Suyama et al 2011) and is completed by the spring of the following year, during our survey period age-1 fish already had an annual ring (Suyama et al 2012a, b). After annual ring identification, the radius of the ring (ROA) was measured from the otolith core to the area where ring formation commenced.…”
Section: Age Determination and Otolith Radius Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The right otolith was embedded in epoxy resin and the incidence of an annual ring determined using light microscopy following Suyama et al (2012a, b). Because formation of the annual ring commences in September (Suyama et al 2011) and is completed by the spring of the following year, during our survey period age-1 fish already had an annual ring (Suyama et al 2012a, b). After annual ring identification, the radius of the ring (ROA) was measured from the otolith core to the area where ring formation commenced.…”
Section: Age Determination and Otolith Radius Measurementmentioning
confidence: 99%
“…The minimum BL of spawning fish collected from Japanese fishing grounds is about 25 cm (Hatanaka 1955); however, individuals collected outside the fishing grounds or season can spawn at about 20 cm (Hotta 1960;Kosaka 2000;Sugama 1957). Based on their body length, these smaller fish could be age-0 (Kurita et al 2004;Nakaya et al 2010;Nemoto et al 2001;Suyama et al 1992Suyama et al , 1996Suyama et al , 2011Watanabe et al 1988) -that is, they have commenced spawning within 1 year of hatching. Minimum maturation size seems to vary according to spawning area and month.…”
Section: Biologymentioning
confidence: 99%
“…Pacific saury is one of the most extensively studied species in the western North Pacific. Previous studies have clarified various aspects of their biology: for example, growth and survival during early life stages (Oozeki and Watanabe, ; Oozeki et al ., , ; Watanabe et al ., ; Suyama et al ., ), age and growth of juveniles and adults (Kosaka, ; Kurita et al ., ; Suyama et al ., ), feeding biology (Sugisaki and Kurita, ), distribution (Huang et al ., ; Tseng et al ., ), migration (Kosaka, ; Kurita et al ., ; Suyama et al ., ), reproduction (Kosaka, ; Kurita, , ), and climate impacts on population dynamics (Oozeki et al ., ; Tian et al ., , ), patchiness structure and mortality rate (Hayashi and Odate, ; Oozeki et al ., ). In addition, Pacific saury is a major species used in bioenergetics models of fish growth and population dynamics in the western North Pacific (Ito et al ., , , ; Kishi et al ., , ; Mukai et al ., ; Werner et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the autumn‐spawned larvae experience higher temperatures and the spring‐spawned larvae experience lower temperatures than the winter‐spawned larvae (Iwahashi et al ., ). Growth and migration of juvenile to adult stages have been studied intensively including their seasonality (Suyama et al ., , , , ). Ito et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the autumn-spawned larvae experience higher temperatures and the spring-spawned larvae experience lower temperatures than the winterspawned larvae (Iwahashi et al, 2006). Growth and migration of juvenile to adult stages have been studied intensively including their seasonality (Suyama et al, 1996(Suyama et al, , 2011(Suyama et al, , 2012. Ito et al (2007) demonstrated that the smallest inter-annual variability of adult wet weight occurred from the winter-spawned cohort among different seasonal cohorts using a bioenergetics growth model; however, larval growth was not carefully tested in the model.…”
Section: Discussionmentioning
confidence: 99%